Antibacterial Activity of Stingless Bee Propolis (Heterotrigona itama) Ethanol Extract on Dental Root Canal Bacteria Growth in Vitro - Takdir, Azizah Qothrunnada; Purnamasari , Cicih Bhakti; Ompusunggu , Novelin Yohana; Paramita, Swandari; Yani, Sinar (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Introduction: Pulp and periapical tissue problems are 7th out of the top 10 diseases. Propolis from stingless bees is a natural substance that has been proven its efficacy in treating the diseases. Additionally, it is categorized safe for humans. This study aimed to determine the antibacterial activity of stingless bee propolis (Heterotrigona itama) ethanol extract on dental root canal bacterial growth in vitro. Method: This study was an experimental study with a posttest-only control group design and consisting of six treatment groups with concentrations of 3,000; 6,000; 12,000; and 24,000 ppm of stingless bee propolis, as well as a positive and negative control. Each treatment was repeated four times. Result: The result showed that there were no clear zones at concentrations of 24,000 ppm, but a clear zones appeared at concentrations of 3,000; 6,000; and 12,000 ppm. Stingless bee propolis ethanol extract is efficient against bacteria. At a concentration of 3,000 ppm, the inhibition zone's maximum circumference was visible.